Analisis Faktor yang Mempengaruhi Return Saham pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Periode 2017-2020 - Christina V Situmorang; Arthur Simanjuntak (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The purpose of this study is to find out and analyze the factors that affect the stock price of banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2020. The subjects of this survey included 39 banking companies by accessing financial statements in audits on the Indonesia Stock Exchange website. The sampling procedure used is a sampling procedure intended for 20 sampling companies in 4 years of observation (2017-2020) with (20 Companies X 4 Years = 80) units of analysis. The data analysis method used is logistic linear regression. Earnings Per Share, Return on Investment, and Price to Book Value (PBV) simultaneously affect the Stock Price by 80.3% based on the results of processing logistic regression data using SPSS 20 software. The remaining 19.7% is affected by other variables. Partially Earning Per Share, Return on Investment, and Price to Book Value (PBV) have a positive and significant effect on Stock Prices.